2020
DOI: 10.1038/s41598-020-69641-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment tests for tumorigenicity of human iPS cell-derived cartilage

Abstract: Articular cartilage damage does not heal spontaneously and causes joint dysfunction. The implantation of induced pluripotent stem cell (iPSC)-derived cartilage (iPS-Cart) is one candidate treatment to regenerate the damaged cartilage. However, concerns of tumorigenicity are associated with iPS-Cart, because the iPSC reprogramming process and long culture time for cartilage induction could increase the chance of malignancy. We evaluated the tumorigenic risks of iPS-Cart using HeLa cells as the reference. Spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In addition, synovial MSCs with trisomy 7 did not induce scaffold‐independence or clonal proliferative potential, nor did they express oncogenes or show an increase in specific senescent cells. Furthermore, similar to the safety test for iPS cells, 33 synovial MSCs with trisomy 7 did not form tumors after transplantation into the subcutaneous region and knees of NOD/SCID mice. Our intensive analysis of synovial MSCs with trisomy 7 for tumorigenesis did not reveal any specific features.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, synovial MSCs with trisomy 7 did not induce scaffold‐independence or clonal proliferative potential, nor did they express oncogenes or show an increase in specific senescent cells. Furthermore, similar to the safety test for iPS cells, 33 synovial MSCs with trisomy 7 did not form tumors after transplantation into the subcutaneous region and knees of NOD/SCID mice. Our intensive analysis of synovial MSCs with trisomy 7 for tumorigenesis did not reveal any specific features.…”
Section: Discussionmentioning
confidence: 61%
“…To assess these possibilities, we subjected chondrocytes isolated from cartilage and generated from a clinical‐grade iPSC line to expansion culture for a prolonged period. Notably, we found that the chondrocytes reached cell senescence, suggesting the cartilage was not contaminated with transformed cells (Takei et al., 2020).…”
Section: Transplantation Of Psc‐derived Chondrocytes or Cartilage Intmentioning
confidence: 82%
“…To measure this number, we used HeLa cells as model transformed cells and transplanted them into nude rat osteochondral defects of 1 mm diameter and 0.5 mm deep. Tumors were not observed when 10 4 or fewer HeLa cells were transplanted, but they did appear if 10 5 HeLa cells were transplanted (Takei et al., 2020). These results indicate that the implantation of up to 10 4 transformed cells in the knee joint does not risk tumor formation if assuming the transformed cells are equivalent to HeLa cells and rat knee is equivalent to human knee.…”
Section: Transplantation Of Psc‐derived Chondrocytes or Cartilage Intmentioning
confidence: 99%
“…Another important aspect for clinical application of these cells is regarding the safety including long-term behavior of these cells and tumorigenic potential once they are transplanted back into the patients [113,114]. There have also been efforts to generate the iPSCs without viral genome integration or even without the use of viruses for delivery of the transcription factors in the cell as the integration of viral genome in recipient cell is associated with tumorigenic consequences [115].…”
Section: Discussionmentioning
confidence: 99%